Large scale instabilities in the electromagnetic drift wave turbulence and transport - Smolyakov, A.I.; Diamond, P.H. (Вопросы атомной науки и техники, 2002)
Large scale structures play an important role in self-organization of drift wave turbulence. Large scale perturbations of plasma flow and magnetic field are spontaneously generated in generic electromagnetic drift wave turbulence via the action of Reynolds stress and electromotive force. Initial large scale perturbations are amplifed by positive feedback due to the modulations of wave packets by the shearing effect of the large scale flow and/or by the perturbed large scale magnetic field. As a result, the propagation of small scale wave packets is accompanied by the instability of a low frequency, long wavelength components. Anomalous transport due to drift wave turbulence may also be unstable with respect to the large scale perturbations of plasma profile. In this case the instability occurs as a result of a positive feedback response of the anomalous flux to the large scale variations of plasma temperature.